Online Quiz Application for Informatics and Information System Students (Task Portal Development) - Maria Bellaniar Ismiati; Latius Hermawan (ICSE (Institute of Computer Sciences and Engineering), 2020)
Abstract: Internet technology is growing rapidly not only in the business world but also in the world of education. The world of education is now widely using technological sophistication and internet-based, such as the process of teaching and learning electronically / known as e-learning. One of the features of e-learning in the teaching and learning process is that it can display material, practice questions, quizzes, or exams electronically. During this time in UKMC, quizzes are often carried out in a conventional manner using paper that will multiply papers that are not used anymore. The purpose of this study is to create an online quiz application for Information Systems students so that lecturers and students can save time in the process and checking. Making an application can help conventional processes be developed by using technology and in real-time. The process of conducting this research starts from Requirements Planning, User Design, Construction, and Testing / Evaluation until finally the final report is made. This research will present a Quiz menu with questions in the form of Multiple Choice and there will be immediately the results of right and wrong answers along with grades and information on whether or not to pass. The results of this study are to reduce the paperless stack and the interaction between students and lecturers is no longer conventional. This research is also a development of the task portal application for Informatics and Information Systems students that was made in the previous year.Abstrak: Teknologi internet semakin berkembang pesat tidak hanya di dunia bisnis saja, tetapi juga di dunia pendidikan. Dunia pendidikan sekarang sudah banyak yang menggunakan kecanggihan teknologi dan berbasis internet, seperti proses belajar mengajar secara elektronik / yang dikenal dengan e-learning. Salah satu fitur e-learning dalam proses belajar mengajar adalah dapat menampilkan materi, soal latihan, kuis, ataupun ujian secara elektronik. Selama ini di UKMC, kuis seringkali dilakukan dengan cara konvensional yaitu menggunakan kertas yang akan memperbanyak kertas-kertas yang tidak digunakan lagi. Tujuan penelitian ini adalah untuk membuat aplikasi quis online bagi mahasiswa Sistem Informasi agar dosen dan mahasiswa dapat menghemat waktu dalam pengerjaannya dan pengecekannya. Pembuatan aplikasi dapat membantu proses konvensional dapat berkembang dengan menggunakan teknologi dan secara real time. Proses pengerjaan penelitian ini dimulai dari Requirements Planning (Perencanaan Persyaratan), User Design, Konstruksi, dan Testing / Evaluasi hingga yang terakhir adalah pembuatan laporan akhir penelitian. Penelitian ini akan menampilkan suatu menu Kuis dengan soal-soal berupa Pilihan Ganda dan nantinya akan langsung ada hasil jawaban yang benar dan salah beserta nilai dan keterangan lulus atau tidaknya. Hasil penelitian ini untuk mengurangi tumpukan kertas (paperless) serta interaksi antara mahasiswa dan dosen tidak secara konvensional lagi. Penelitian ini juga merupakan pengembangan dari aplikasi portal tugas bagi mahasiswa Informatika dan Sistem Informasi yang telah dibuat di tahun sebelumnya.